Inovasi Pengembangan Model Pendidikan Islam Transformatif Berbasis Penelitian dan Pengabdian Kepada Masyarakat (Pkm) - Akhmad Arifudin; Nur Cholid; M Ahsanul Husna (Ikatan Dai Indonesia, 2026)
Contemporary Islamic education is required to produce graduates who possess not only academic and spiritual competencies but also the ability to critically and effectively address various social challenges. One strategic approach is the development of a transformative Islamic education model that integrates research and community service activities as essential components of the learning process. This study aims to analyze and formulate an innovative model of transformative Islamic education based on research and community service that is relevant to the demands of twenty-first-century education. The study employs a qualitative approach using a library research method. Data were collected from scholarly books, national and international journal articles, and relevant studies concerning Islamic education, transformative education, research-based learning, and community engagement. The data were analyzed through content analysis to identify key concepts and develop an integrative educational model. The findings reveal that a transformative Islamic education model based on research and community service can be developed through the integration of philosophical foundations, curriculum design, learning processes, character and spiritual development, and social partnerships. Research serves as a source of innovation and knowledge development, while community service functions as a medium for applying knowledge to real-life contexts. The model promotes the implementation of Research-Based Learning, Problem-Based Learning, Project-Based Learning, and Service Learning approaches aimed at preparing learners to become agents of social transformation. The implementation of this model contributes to the enhancement of critical thinking, creativity, social responsibility, religiosity, and the overall relevance of Islamic education to societal needs. Therefore, transformative Islamic education based on research and community service represents an innovative strategy for fostering contextual, participatory, and sustainable Islamic education.